Feasibility of Development of a Cohort in a Rural Area of Sub-Himalayan Region of India to Assess the Emergence of Cardiovascular Diseases Risk Factors. (22nd January 2014) - Bhardwaj, Ashok Kumar; Kumar, Dinesh; Raina, Sunil Kumar; Bhushan, Satya; Chander, Vishav; Sharma, Sushant
Abstract : Introduction . Rural area of India is facing epidemiological transitions due to growth and development, warranting a longitudinal study to assess the development of CVDs risk factors. Objective. Feasibility of setting up a rural cohort for the assessment and development of biochemical risk factors for CVDs. Methodology . In Himachal Pradesh, house-to-house surveys were carried out in six villages for anthropometry and assessment of lipid profile. All the information was stored in specifically designed web-based software, which can be retrieved at any time. Results . A total of 2749 individuals of more than 20 years of age were recruited with a 14.3% refusal rate. According to Asian criteria, measured overweight and obesity (BMI > 27.5 kg/m 2 ) were 44.9% and 10.5%, respectively. Obesity was significantly more (P = 0.01 ) among females (11.7%) as compared to males (8.4%). The prevalence of prehypertension and hypertension was observed to be 16.3% and 37.4%, respectively. Eighty percent of individuals had borderline (46.5%) to high (35.4%) level of triglycerides (TGs). Elevated total cholesterol (TC) and low density lipoprotein (LDL) level were observed among 30.0% and 11.0% individuals only. Conclusion . A high prevalence of biochemical risk factors for CVDs in a rural area urges establishment of an effective surveillance system.